Application of poultry secondary processed products on the example bile - Bondar, Svitlana (My University, 2014)
Recently the meat industry has made a significant progress in the development of science, technology improvement, technology, production and scientific organization of labor.
Keywords: secondary processed products; bile; poultry; вторинні продукти переробки; жовч